Preparation of supercapacitor electrodes through selection of graphene surface functionalities - Lai, Linfei (2013)
In order to investigate the effect of graphene surface chemistry on the electrochemical performance of graphene/polyaniline composites as supercapacitor electrodes, graphene oxide (G-O), chemically reduced G-O (RG-O), nitrogen-doped RG-O (N-RG-O), and amine-modified RG-O (NH2-RG-O) were selected as carriers and loaded with about 9 wt % of polyaniline (PANi). The surface chemistry of these materials was analyzed by FTIR, NEXAFS, and XPS, and the type of surface chemistry was found to be important for growth of PANi that influences the magnitude of increase of specific capacitance. The NH2-RG-O/PANi composite exhibited the largest increase in capacitance with a value as high as 500 F g–1 and good cyclability with no loss of capacitance over 680 cycles, much better than that of RG-O/PANi, N-RG-O/PANi, and G-O/PANi when measured in a three-electrode system. A NH2-RG-O/PANi//N-RG-O supercapacitor cell has a capacitance of 79 F g–1, and the corresponding specific capacitance for NH2-RG-O/PANi is 395 F g–1. This research highlights the importance of introducing −NH2 to RG-O to achieve highly stable cycling performance and high capacitance values.